Combination of Fusiform Capsulectomy of the Posterior Capsule and Percutaneous Flexion Tendon Release in the Treatment of Fused Knee with Severe Flexion Contracture During Total Knee Arthroplasty—A Report of Six Cases - Chen, Qun-Qun; He, Min-Cong; Cao, Zheng; Kong, Xiang-Peng; Wang, Hai-Bin; Chai, Wei (Frontiers in Surgery, 2022)
Purpose This clinical research aims to assess the safety and efficacy of a combination of fusiform capsulectomy of the posterior capsule and percutaneous flexion tendon release in the treatment of a fused knee with severe flexion contracture during total knee arthroplasty (TKA). Methods A retrospective analysis was performed in three patients (six knees) who had preoperative severe bony fused flexion contracture (>80°) prior to TKA and received a combination of fusiform capsulectomy of posterior capsule and percutaneous flexion tendon release during TKA between January 2016 and December 2019. The range of motion (ROM), knee functional score, postoperative complications, and radiographic results were evaluated. Result Three patients (six knees) were enrolled in this study. The mean duration of follow-up was 42.83 ± 15.77 months. The postoperative knee ROM was 100.0 (76.0, 102.75) (p < 0.01). The knee society score (KSS) clinical score increased from a preoperative 30.0 (25.0, 36.0) to a postoperative 64.0 (65.0, 78.0) (p < 0.01), and the KSS function score increased from a preoperative 0.0 (0.0, 30.0) to a postoperative 55.0 (40.0, 55.0) (p < 0.01). No implant loosening, infection, neurovascular complications, or revision were recorded in the cohort until the last follow-up. Conclusion The technique of a combination of fusiform capsulectomy of the posterior capsule and percutaneous flexion tendon release is an effective and safe method during primary TKA for a fused knee with severe flexion contracture.